2022
DOI: 10.1002/advs.202203396
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Modal Locomotion of Caenorhabditis elegans by Magnetic Reconfiguration of 3D Microtopography

Abstract: Miniaturized untethered soft robots are recently exploited to imitate multi‐modal curvilinear locomotion of living creatures that perceive change of surrounding environments. Herein, the use of Caenorhabditis elegans (C. elegans) is proposed as a microscale model capable of curvilinear locomotion with mechanosensing, controlled by magnetically reconfigured 3D microtopography. Static entropic microbarriers prevent C. elegans from randomly swimming with the omega turns and provide linear translational locomotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Besides acting as the legs of soft-robots, magnetic micropillars also could serve as microbarriers to guide the multi-modal locomotions of the C. elegans, including linear translation, navigating movement, circumventing movement, and climbing. [154]…”
Section: Microrobotsmentioning
confidence: 99%
“…Besides acting as the legs of soft-robots, magnetic micropillars also could serve as microbarriers to guide the multi-modal locomotions of the C. elegans, including linear translation, navigating movement, circumventing movement, and climbing. [154]…”
Section: Microrobotsmentioning
confidence: 99%
“…The pre-tilt in particle alignments provides a preferential and uniform directionality of the magnetomechanical actuation under an external magnetic field orthogonal (𝜃 B = 90°) to l bd . [26,27,[30][31][32] Tilting at −10°and +10°of the alignments leads to a counterclockwise reverse (Figure 2b; and Figure S3a, Supporting Information), and clockwise forward (Figure 2c; and Figure S3c, Supporting Information) magnetic actuation, respectively. This design determines whether the top surface of the actuated microdenticles is flat-or riblet-textured.…”
Section: Biomimetic Microfabrication Of Sharkskin With Complex Archit...mentioning
confidence: 99%
“…To this end, bristled microdenticles are prepared using polymeric composites comprising ferromagnetic iron (Fe) particles and polydimethylsiloxane (PDMS) for uniform and large-area microfabrication. The Fe particles are vertically aligned within the mechanically soft Fe/PDMS microdenticles and staggered on a magnetically inert PDMS dermis substrate to generate a magnetic torques [26][27][28][29][30][31][32] under an external magnetic field. The actuation with the high torques enables the microdenticles to overlap, and then, fixing this overlapping follows because the overlapped microdenticles start reverting to their original bristled states once the external magnetic field is removed.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to C. elegans' locomotion in the presence of MF, besides the impact of the earth's MF [26,55], the literature is sparse. It is reported that nematodes are not affected by mild static MF [27] and that their locomotion can be manipulated by magnetically responsive structures [56], but other than that not much is known about the impact of MF on C. elegans' locomotive machinery.…”
Section: Introductionmentioning
confidence: 99%